Pengaruh Gaya Kepemimpinan Dan Pelatihan Terhadap Motivasi, Serta Dampaknya Pada Kinerja Guru Di Sekolah Islam Terpadu Insan Mandiri Cendekia Palembang - Nurrizka istiqhoro; Edizal AE; Djatmiko Noviantoro (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
This study aims to determine and analyze the influence of leadership style and training on motivation, as well as its impact on teacher performance in the Integrated Islamic School of Insan Mandiri Cendekia Palembang, either simultaneously or partially. This research method uses a quantitative approach with data collection methods using questionnaires or questionnaires based on the Likert scale. The analysis technique uses SmartPLS with validity test, reliability test, and hypothesis testing to test the t test and F test. The results of the research based on the results of quantitative data processing, it is known that the data passed the validity and reliability tests. Leadership style has a positive and significant effect on work motivation. This is indicated by the t-count is 3.744 1.96 and the p-value is 0.000 <0.05, meaning that the hypothesis is accepted, so it can be concluded that there is an influence of Leadership Style on Teacher Work Motivation at the Integrated Islamic School of Insan Mandiri Cendekia Palembang. Training has a positive and significant effect on teacher motivation at the Integrated Islamic School for Insan Mandiri Cendekia Palembang, this is indicated by the t statistic of 2.383 1.96 or P-value 0.018 < 0.05. it means that the hypothesis is accepted, so that it is concluded that there is an effect of training on teacher work motivation at the Integrated Islamic School for Insan Mandiri Cendekia Palembang. Leadership Style has an effect on Teacher Performance at the Integrated Islamic School of Insan Mandiri Cendekia Palembang, this is shown by the t-statistic of 3.241 1.96 or P-value 0.001 < 0.05, meaning that the hypothesis is accepted, so it can be concluded that there is an influence of Leadership Style on Teacher Performance in Schools Integrated Islam, Independent Scholar of Palembang. Training has a positive and significant effect on teacher performance at the Integrated Islamic School of Insan Mandiri Cendekia Palembang, this is indicated by the t statistic of 2.710 1.96 or P-value 0.007 < 0.05. it means that the hypothesis is accepted, so that it is concluded that training has an effect on teacher performance at the Integrated Islamic School of Insan Mandiri Cendekia Palembang, motivation has a positive and significant effect on teacher performance at the Integrated Islamic School of Insan Mandiri Cendekia Palembang, this is shown by the t statistic of 3.112 1.96 or P-value 0.002 < 0.05. it means that the hypothesis is accepted, so that it can be concluded that motivation has an effect on teacher performance at the Integrated Islamic School of Insan Mandiri Cendekia Palembang.